2020
DOI: 10.3892/ijmm.2020.4749
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑202 inhibits endometrial stromal cell migration and invasion by suppressing the K‑Ras/Raf1/MEK/ERK signaling pathway

Abstract: The enhanced migratory ability of endometrial stromal cells (ESCs) is a key factor in the formation of functional endometrium-like tissues outside the uterine cavity during endometriosis (EMS). Although accumulating evidence has suggested the importance of microRNAs (miRNAs) in the pathogenesis of EMS, the role of particular miRNAs in the invasiveness of ESCs remain poorly understood. In the present study, the function of miRNAs in the invasiveness of ESCs, along with the associated underlying mechanism involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…On the other hand, in NSCLC cells, overexpression of miR-202 was found to inhibit the Ras/mitogen activated protein kinase (MAPK) pathway via targeting the KRAS gene, thereby expanding apoptosis signaling induced by cisplatin [ 47 ]. This aligns with the observation that endometrial stromal cell migration and invasion is suppressed by the K-Ras/Raf1/MEK/ERK signaling pathway [ 93 ]. Additionally, ionizing radiation (IR) was reported to activate K-Ras/ERK signaling downregulated miR-202 and miR-185 expression, which, in turn, upregulated CD44.…”
Section: Mechanistic Pathways Involving Mir-202 As a Tumor Suppressorsupporting
confidence: 90%
“…On the other hand, in NSCLC cells, overexpression of miR-202 was found to inhibit the Ras/mitogen activated protein kinase (MAPK) pathway via targeting the KRAS gene, thereby expanding apoptosis signaling induced by cisplatin [ 47 ]. This aligns with the observation that endometrial stromal cell migration and invasion is suppressed by the K-Ras/Raf1/MEK/ERK signaling pathway [ 93 ]. Additionally, ionizing radiation (IR) was reported to activate K-Ras/ERK signaling downregulated miR-202 and miR-185 expression, which, in turn, upregulated CD44.…”
Section: Mechanistic Pathways Involving Mir-202 As a Tumor Suppressorsupporting
confidence: 90%
“…B cells expressing CD25 spontaneously secrete immunoglobulins of the IgA, IgG and IgM subclasses and have an enhanced migratory capacity compared to CD25(-) B cells ( 55 ). The increased migratory capacity of endometrial stromal cells (ESCs) is a fundamental determinant in the development of functional endometrium-like tissue outside the uterine cavity in EMS ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 Recently, reduced expression of miR-202 in patients with endometriosis has been shown to promote the migration and infiltration of endometriotic cells through the activation of K-Ras-Raf-1-MEK. 32 In addition, MEK and AKT are involved in the proliferation of endometriotic stromal cells, and the combined use of an MEK inhibitor and an AKT inhibitor results in additive inhibition of endometriotic stromal cell proliferation. 33 In the present study, upregulation of both TNFR1 and TNFR2 was observed.…”
Section: Discussionmentioning
confidence: 99%